An evaluation of experiences and views of Scottish leadership training opportunities amongst primary care professionals. Issue 3 (4th May 2017) - Power, Ailsa; Allbutt, Helen; Munro, Lucy; MacLeod, Marion; Kennedy, Susan; Cameron, Donald; Scoular, Ken; Orr, Graham; Gillies, John
Abstract: Aim : To determine experiences of leadership training of six primary care professions in Scotland and consider future development.Methods: A questionnaire on previous leadership course attendance and future intentions was distributed to community pharmacists, general dental practitioners, general practitioners, practice nurses, practice managers and optometrists. Analysis comprised descriptive statistics for closed questions and management of textual data.Results: Formal leadership training participation was fairly low except for practice managers. Leadership was perceived to facilitate development of staff, problem-solving and team working. Preference for future delivery was similar across the six professions with e-modules and small group learning being preferred. Time and financial pressures to undertake courses were common barriers for professionals.Conclusion: Leadership is key to improve quality, safety and efficiency of care and help deliver innovative services and transformative change. To date, leadership provision for primary care professionals has typically been patchy, uni-disciplinary in focus and undertaken outwith work environments. Future development must reflect needs of busy primary care professionals and the reality of team working to deliver integrated services at local level.